Upregulation of MRNA TNF-α in Skeletal Muscle Tissue of Streptozotocin-Induced Diabetic RAT - Akbar Satria Fitriawan; Christin Wiyani; Endang Nurul Syafitri; Ririn Wahyu Widayati (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Inflammation is a molecular mechanism that linking obesity and ageing with insulin resistance in type 2 diabetes mellitus (DM). Although type 1 DM is primarily caused by insulin deficiency, but insulin resistance also prominent feature in this disease. It is not fully understood whether inflammation also contribute in insulin resistance phenotype in type 1 DM. This study aimed to assess mRNA TNF-α expression in the skeletal muscle tissue of type 1 diabetes mellitus rat model.This in-vivo study used 18 adults male wistar rats. The study conducted at Department of Anatomy, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada from July to October 2020. Male Wistar rats divided into control group (CDM, n=6), and diabetes mellitus group which is divided into 1-month DM group (DM1M, n=6), and 2-month DM group (DM2M, n=6). The DM model was conducted through single intraperitoneal injection of Streptozotocin 60 mg/kg Body Weight (BW). At the end of study, rats were sacrificed and the gastrocnemius muscle was harvested. The expression of mRNA TNF-α was measured by RT-PCR. Statistical analysis was conducted using One Way ANOVA test. Blood glucose level were significantly higher in DM groups compared to control group (p<0.05). The body weight of DM groups was significantly lower after 1 month and 2 months DM period compared to control group (p<0.05). DM groups demonstrated upregulation of mRNA TNF-α compared to control group (p<0.05). Type 1 diabetes mellitus model demonstrated upregulation of mRNA TNF-α in skeletal muscle tissue.